APPLICATION OF MODEL PROBLEM BASED LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES IN SUBTEMA ENERGY AND ITS CHANGES - Wida Setiawati; Dedi Priatna; Anugrah Ramadhan Firdaus (IKIP Siliwangi, 2018)
This study aims to improve learning outcomes of students through a learning model of problem-based learning on the sub-theme energy and change. This research was conducted in class III SD Muhammadiyah 4 Bandung and against the background circumstances of students are lacking in learning outcomes in the learning because teachers still use the learning that is conventional, that is, by using the lecture method, so that the involvement of learners in the learning was minimal. By using the model of Problem Based Learning can improve learning outcomes of students, because, in this model, the students become the center in the process of learning, stimulating learners to think critically, and to deepen their knowledge about what they know and what they need to know to solve the problem. In addition to its model of problem-based learning can also increase the activity and learning outcomes of students, help, develop skills to solve problems, and develop the skills to communicate orally. The conclusions obtained from this study is that the use of the model of problem-based learning can improve learning outcomes of students. Thus, the application of learning model problem based learning in sub-theme energy and amendments can be used as an alternative method of learning to be applied in Elementary School.